Outcomes of extensive hybridization and introgression in Epidendrum (Orchidaceae): can we rely on species boundaries? - Yesenia Vega; Isabel Marques; Sílvia Castro; João Loureiro (PLoS ONE, 2013)
Hybridization has the potential to contribute to phenotypic and genetic variation and can be a major evolutionary mechanism. However, when hybridization is extensive it can also lead to the blurring of species boundaries and the emergence of cryptic species (i.e., two or more species not distinguishable morphologically). In this study, we address this hypothesis in Epidendrum, the largest Neotropical genus of orchids where hybridization is apparently so common that it may explain the high levels of morphological diversity found. Nonetheless, this hypothesis is mostly based on the intermediacy of morphological characters and intermediacy by itself is not a proof of hybridization. Therefore, in this study, we first assessed the existence of hybrids using cpDNA and AFLP data gathered from a large-scale sampling comprising 1038 plants of three species of Epidendrum (E. calanthum, E. cochlidium and E. schistochilum). Subsequently, a Bayesian assignment of individuals into different genetic classes (pure species, F1, F2 or backcross generations) revealed that hybrid genotypes were prevalent in all sympatric populations. In most cases, parental species were not assigned as pure individuals, rather consisting in backcrossed genotypes or F1 hybrids. We also found that reproductive barriers are apparently very weak in Epidendrum because the three species largely overlapped in their flowering periods and interspecific crosses always produced viable seeds. Further, hybridization contributed to enhance floral variability, genome size and reproductive success since we found that these traits were always higher in hybrid classes (F1, F2 and backcrosses) than in pure parental species, and offer an explanation for the blurring of species boundaries in this genus of orchids. We hypothesize that these natural hybrids possess an evolutionary advantage, which may explain the high rates of cryptic species observed in this genus.